Exploring Structure–Property Relationships of Silver 4‐(Phenylethynyl)pyridine Complexes. Issue 13 (3rd April 2017) - Knichal, Jane V.; Gee, William J.; Cameron, Christopher A.; Skelton, Jonathan M.; Gagnon, Kevin J.; Teat, Simon J.; Wilson, Chick C.; Raithby, Paul R.; Burrows, Andrew D.
Abstract : Silver(I) salts demonstrate a strong preference for forming linear complexes when reacted with 4‐(phenylethynyl)pyridine (pep). The packing of these complexes was found to be strongly influenced by the counteranions, namely PF6 –, BF4 –, NO2 –, NO3 –, MeCO2 –, CF3 CO2 –, MeSO3 –, Tos – and SCN – . This study evaluates a family of twelve solid‐state structures that exhibit varying metal‐to‐ligand ratios, [Ag(pep)2 ][PF6 ]· MeCN, [Ag(pep)2 ][PF6 ], [Ag(pep)2 ][BF4 ], [Ag(pep)2 ][Ag(NO2 )2 ], [Ag(pep)2 ][NO3 ]· 2H2 O, [Ag(pep)2 ][Ag(NO3 )2 ], [Ag(pep)2 (MeCO2 )]· 3H2 O, [Ag(pep)2 ][CF3 CO2 ], [Ag(pep)2 ][CF3 SO3 ], 2{[Ag(pep)2 ][Tos]}· pep and [Ag(pep)(SCN)]. This family has enabled general trends and noteworthy packing‐induced structure–property relationships to be elucidated. Highlights include two instances of single‐crystal‐to‐single‐crystal transformations, one of which occurs with a colour change. This change in crystal colour has been further explored using first‐principles computational modelling. Abstract : This work explores the effects of anion variation on silver complexes of 4‐(phenylethynyl)pyridine, linking structure with property, such as the propensity for single‐crystal‐to‐single‐crystal transformations.